2000
DOI: 10.1183/09031936.00.15109800
|View full text |Cite
|
Sign up to set email alerts
|

Nasal ventilation in COPD exacerbations: early and late results of a prospective, controlled study

Abstract: Noninvasive positive pressure mechanical ventilation (NIPPV) in exacerbated chronic obstructive pulmonary disease (COPD) has been investigated early and after 1 yr of follow-up.To this end, 30 patients were enrolled in a prospective, controlled trial: 15 had early administration of NIPPV (Group A), 15 had medical therapy only (Group B); assignment was made on the basis of equipment availability only.In-hospital mortality, need for endotracheal intubation and mean length of hospitalization were lower in Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 22 publications
(28 reference statements)
3
32
0
7
Order By: Relevance
“…Three studies have suggested that the use of NIV is associated with a better 1-yr survival compared to standard ICU therapy [33,34] or invasive mechanical ventilation [35]. The recent study of CONTI et al [21] confirms these findings.…”
Section: Long-term Survivalmentioning
confidence: 93%
“…Three studies have suggested that the use of NIV is associated with a better 1-yr survival compared to standard ICU therapy [33,34] or invasive mechanical ventilation [35]. The recent study of CONTI et al [21] confirms these findings.…”
Section: Long-term Survivalmentioning
confidence: 93%
“…BARDI et al [8] found no significant differences in hospital outcome between NIV and conventional therapy in a study of 30 patients with COPD, with the majority of patients in both groups recovering without the need for invasive ventilation. Because there was no ICU on site NIV was started early, and as the mean pH in the two groups were 7.36 and 7.39 and no patient in either group had a pH v7.30 these results are not surprising.…”
mentioning
confidence: 93%
“…In more severely ill patients (pH<7.25), the rate of NPPV failure was inversely related to the severity of respiratory acidosis, rising up to 52%-62% (Conti et al 2002;Squadrone et al 2004). In patients with ''mild'' exacerbations, not complicated by respiratory acidosis, the use of NPPV was investigated in few studies, including patients in large majority with pH>7.35, which failed to demonstrate a better effectiveness of NPPV than standard medical therapy in preventing the occurrence of ARF (Bardi et al 2000;Keenan, Powers, & McCormack 2005). Guidelines recommend the use of NPPV in addition to usual care in patients who have a severe exacerbation of COPD (pH<7.35 and relative hypercarbia) (grade 1A recommendation) (Keenan et al 2011).…”
Section: Acute Respiratory Failure/exacerbation Of Copdmentioning
confidence: 99%